2017
DOI: 10.1073/pnas.1609844114
|View full text |Cite
|
Sign up to set email alerts
|

HY5, a positive regulator of light signaling, negatively controls the unfolded protein response inArabidopsis

Abstract: Light influences essentially all aspects of plant growth and development. Integration of light signaling with different stress response results in improvement of plant survival rates in ever changing environmental conditions. Diverse environmental stresses affect the protein-folding capacity of the endoplasmic reticulum (ER), thus evoking ER stress in plants. Consequently, the unfolded protein response (UPR), in which a set of molecular chaperones is expressed, is initiated in the ER to alleviate this stress. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
102
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(115 citation statements)
references
References 39 publications
5
102
0
Order By: Relevance
“…integrates a range of external stimuli and hormone signals, which affect plant growth in 379 both positive and negative ways (Liu et al, 2007a,b;Che et al, 2010;Parra-Rojas et al, 380 2015;Zhou et al, 2015;Deng et al, 2106;Meng et al, 2017;Nawkar et al, 2017). 381 20 Therefore, it is likely that multiple signaling pathways conjunctly determine root 382 elongation through UPR regulation in plants via bZIP17 and bZIP28.…”
Section: Endotransglucosylase/hydrolase (Xth) and Expansin (Exp)mentioning
confidence: 99%
“…integrates a range of external stimuli and hormone signals, which affect plant growth in 379 both positive and negative ways (Liu et al, 2007a,b;Che et al, 2010;Parra-Rojas et al, 380 2015;Zhou et al, 2015;Deng et al, 2106;Meng et al, 2017;Nawkar et al, 2017). 381 20 Therefore, it is likely that multiple signaling pathways conjunctly determine root 382 elongation through UPR regulation in plants via bZIP17 and bZIP28.…”
Section: Endotransglucosylase/hydrolase (Xth) and Expansin (Exp)mentioning
confidence: 99%
“…This inhibition is mediated by competition for binding to the G-box element (CACGTG) displayed within the ERSE motif(s) in the promoters of the UPR genes. Under ER stress conditions, HY5 undergoes proteasomal degradation, upon which bZIP28 can bind to the ERSE motif(s) and activate the UPR (Nawkar et al, 2017). Conversely, a similar scenario has been reported for JA-inducible genes by Van der Does et al (2013) (ORA 59).…”
Section: Induced Ts Gene Expression?mentioning
confidence: 62%
“…Here, we also attempted to determine how the bZIP and TSAR TFs interact to modulate TS biosynthesis. It has been demonstrated in A. thaliana that under nonstressed conditions, the activity of bZIP28 in for instance the UPR, which causes ER stress, is inhibited by ELONGATED HYPOCOTYL 5 (HY5), another bZIP TF (Nawkar et al, 2017). This inhibition is mediated by competition for binding to the G-box element (CACGTG) displayed within the ERSE motif(s) in the promoters of the UPR genes.…”
Section: Induced Ts Gene Expression?mentioning
confidence: 99%
“…Interestingly, we found that Pt667 harbors significant number of abiotic stress responsive components particularly the light responsive elements such as ACE, AE, G‐box, GAG‐motif, HSE, MBS, SpnI and TCT‐motif. Earlier studies in various plant systems have demonstrated that these elements involved in light responsiveness (Li et al, ; Nawkar et al, ; L. W. Wang, He, et al, ). It has been reported that light plays a crucial role in regulating carotenoid biosynthetic pathway and in silico analysis showed the presence of various light‐response motif in Pt667, thereby highlighted the role of these promoters on driving carotenogenic genes which warrant further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we found that Pt667 harbors significant number of abiotic stress responsive components particularly the light responsive elements such as ACE, AE, G-box, GAG-motif, HSE, MBS, SpnI and TCT-motif. Earlier studies in various plant systems have demonstrated that these elements involved in light responsiveness Nawkar et al, 2017;L. W. Wang, He, et al, 2017b).…”
Section: Discussionmentioning
confidence: 99%